Pengaruh Motor Relearning Program (MRP) Terhadap Peningkatan Keseimbangan Duduk Pasien Pasca Stroke - RISTIAWATI, Rahma Hanifa, Umi Budi Rahayu, SSt. Ft. SPd. M. Kes, Wahyuni, S.Fis., M.Kes (2015)
Background: Stroke is a disorder of the nervous system are the most common and major cause of functional activity disorders in adults. Post-stroke problems posed to human life is very complex. The presence of disorders of the brain vital functions such as impaired coordination, posture control disorders, impaired sensation, balance disorders are like sitting balance will decrease the functional activity of individual daily. Exercise Motor Relearning Program can make the learning process as well as the functional activity applied basic premise that the capacity of the brain is able to adapt as well as the reorganization and targeted exercises can be cured and improved. Objective: To determine of Motor Relearning Program for enhancement sitting balance of post-stroke patients. Methods: This study used a method Single Case Research with A-B-A approach, they are A1 as the first baseline, B as giving a treatment, and A2 as the final baseline. Respondents in this study were 2 people. The study was conducted as much as 9 times for 3 weeks. Results: Giving MRP on both respondents in getting pre-test score of at least 20, maximum 23 pre-test value, while the post-test score of at least 29 and a maximum value of 38. With the post-test mean pre-test to post-test 21.5 and 33.5. Conclusion: There was an effect of Motor Relearning Program for enhancement sitting balance of post stroke patients.